1999
DOI: 10.1016/s0022-5223(99)70436-8
|View full text |Cite
|
Sign up to set email alerts
|

Vesnarinone and amrinone reduce the systemic inflammatory response syndrome

Abstract: Vesnarinone and amrinone, which are used clinically for their inotropic and vasodilating properties, may be useful to limit inflammatory activation and consequent organ dysfunction. Structure-activity and/or pharmacokinetic between the compounds may be important, particularly in preventing inflammatory signaling within certain tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…In keeping with previous studies with iNOS inhibitors, these findings suggest that NO production during endotoxemia is not a primary cause of systemic hypotension (14,15). Our data of induced iNOS activity in the rabbit heart are in keeping with previous findings by Takeuchi et al (16). Moreover, increased cardiac content of cyclic guanosine 3',5'-monophosphate, likely caused by iNOS activation, was found in rabbit cardiac myocytes incubated for 6 hrs with LPS (17).…”
Section: Discussionsupporting
confidence: 93%
“…In keeping with previous studies with iNOS inhibitors, these findings suggest that NO production during endotoxemia is not a primary cause of systemic hypotension (14,15). Our data of induced iNOS activity in the rabbit heart are in keeping with previous findings by Takeuchi et al (16). Moreover, increased cardiac content of cyclic guanosine 3',5'-monophosphate, likely caused by iNOS activation, was found in rabbit cardiac myocytes incubated for 6 hrs with LPS (17).…”
Section: Discussionsupporting
confidence: 93%
“…This agent exhibits potent immunomodulatory activity, as indicated by the suppression of NK cell activity (2,3), endotoxin-induced production of inflammatory cytokines (4 -10), and nitric oxide synthase from macrophages (11,12) and cardiac myocytes (11,13), and it abrogate E-selectin expression in endothelial cells (5). These immunosuppressive effects of vesnarinone have been suggested to contribute to its activity against CHF (9), prolongation of cardiac allograft survival (14,15), and suppression of systemic inflammation (16). Vesnarinone also causes agranulocytosis by impairing stromal functions and cytokine inhibition (17,18) and inhibits immune-mediated hepatic injury (19).…”
Section: -Piperazinyl]-2(1h)-quinolinone; Also Called Opc-8212mentioning
confidence: 99%
“…Indeed, several in vitro studies 10 -12 have shown that vesnarinone suppresses the production of TNF-␣ and IL-6 in various human cell lines, including peripheral lymphocytes, monocytes, T-cell lines, and microglial cells. Moreover, an in vivo study 23 of endotoxemia in rabbits showed that IV vesnarinone reduced the circulating levels of TNF-␣. Although the reasons for the discrepancy between the previous in vitro/in vivo findings are not clear, there are several possible explanations.…”
Section: Discussionmentioning
confidence: 99%